Investigation of biomarkers for impending fluid overload in a feline acute haemorrhage-resuscitation model. (November 2021) - Zeiler, Gareth E.; Dzikiti, Brighton T.; Kamerman, Peter; Pohlin, Friederike; Buck, Roxanne K.; Fuller, Andrea
Abstract: Objective: To determine biomarkers for impending fluid overload during intravenous fluid administration in a feline haemorrhage-resuscitation model. Study design: Randomized crossover study. Animals: A group of six domestic cats (mean age and weight: 21 months; 4.9 kg, respectively). Methods: The cats underwent three treatments, 2 months apart. They were anaesthetized and instrumented to measure a range of physiological, blood gas, haematological and biochemical variables over time. Samples were taken during a health check, before haemorrhage, after haemorrhage and then at 30 minute intervals during fluid resuscitation and 24 hours later. The three treatments were: 1) control, sham haemorrhage and resuscitation; 2) lactated Ringer's solution (LRS); and 3) 6% tetrastarch 130/0.4 (Vol) where the cats underwent a controlled haemorrhage then resuscitation by administering LRS and Vol at 60 and 20 mL kg –1 hour –1, respectively, for 120 minutes. Fluid overload was identified by nasal discharge and radiographic evidence. Biomarkers were variables that exceeded the reference interval for cats during treatment. Potential biomarkers were analysed using receiver operating characteristic curves ( p < 0.05). Results: Mean ± standard deviation total blood loss was 10.2 ± 2.3, 29.3 ± 9.0 and 29.1 ± 6.3 mL kg –1 for control, LRS and Vol, respectively. The total volume of LRS and Vol administered was 120 and 40 mL kg –1, respectively. Haematocrit, albumin, magnesium, chloride-to-sodium ratio and sodium-chloride difference were identified as potential biomarkers. These variables exceeded the reference intervals from 30 minutes of resuscitation onwards. A chloride-to-sodium ratio > 0.84 was the most sensitive (90%) and specific (75%) of all potential biomarkers. Conclusions and clinical relevance: Changes in physiological variables, haematocrit and albumin were poor biomarkers of impending fluid overload compared with electrolytes. Finding the ideal biomarker to identify impending fluid overload of commonly used intravenous fluids should improve the safety of their administration in cats.